THE STRATEGIC ROLE OF FRONT-END ENGINEERS IN SOFTWARE PROTOTYPING: A CROSS-FUNCTIONAL ANALYSIS - Nikhil Sripathi Rao, (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY (IJCET), 2024)
This article examines the pivotal role of front-end engineers in modern software prototyping processes, exploring their unique position at the intersection of technical implementation and user experience design. We look at how front-end engineers help improve prototyping by analyzing software development teams and industry professionals over time. The article reveals significant improvements in prototype development efficiency, including an increase in successful product launches, higher stakeholder satisfaction, and a reduction in post-development design changes when front-end engineers lead prototyping initiatives. The research in this article demonstrates how front-end engineers' dual competency in technical implementation and design principles enables them to bridge critical gaps in the product development lifecycle, leading to more streamlined development processes and improved final products. The article also highlights emerging trends in prototype development methodologies, team structures, and collaboration patterns, providing valuable insights for organizations seeking to optimize their software development processes. These findings contribute to the growing body of knowledge on modern software development practices while offering practical recommendations for leveraging front-end engineering expertise in prototyping initiatives.